2021
DOI: 10.1155/2021/6666323
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at ST36 Improve the Gastric Motility by Affecting Neurotransmitters in the Enteric Nervous System in Type 2 Diabetic Rats

Abstract: Electroacupuncture (EA) can effectively relieve hyperglycemia and gastric emptying disorders in diabetic gastroparesis (DGP). However, the effect of EA on type 2 diabetes mellitus (T2DM) gastroparesis and its mechanism in the enteric nervous system (ENS) are rarely studied. We investigated the therapeutic effect of EA at ST36 and its effect on the main inhibitory and excitatory neurotransmitters in the ENS in DGP rats. Male Sprague-Dawley (SD) rats were fed a high-fat diet for 2 weeks and injected with strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“… Ji et al (2013) concluded that EA ST36 produces an up-regulation of anorexigenic factor POMC production in the NTS/HN, which inhibited food intake and reduced body weight. Meanwhile, Zhang Y. et al (2020) and Han et al (2021) also found the similarly result, which suggest that single point stimulation at ST36 can reduce body weight. In this experiment, it was observed that the body weight of the HFD + EA group only a decreased compared with the HFD group during EA, suggesting that a single EA treatment could not restore the body weight of model mice to a normal level.…”
Section: Discussionmentioning
confidence: 63%
“… Ji et al (2013) concluded that EA ST36 produces an up-regulation of anorexigenic factor POMC production in the NTS/HN, which inhibited food intake and reduced body weight. Meanwhile, Zhang Y. et al (2020) and Han et al (2021) also found the similarly result, which suggest that single point stimulation at ST36 can reduce body weight. In this experiment, it was observed that the body weight of the HFD + EA group only a decreased compared with the HFD group during EA, suggesting that a single EA treatment could not restore the body weight of model mice to a normal level.…”
Section: Discussionmentioning
confidence: 63%
“…Another hypothesis is that a general anesthesia-induced decrease in leptin levels was counteracted by acute EA at back acupoints. Plasma insulin levels decreased in all EA treatments except for leg acupoints and the insulin drop (after-before) was higher in control than in the back and leg treatments, which is surprising considering that decreased insulin levels and insulin resistance were demonstrated in obese women [ 43 ] and rats [ 47 ] after EA on limbs. It is important to remind here that the minipigs used for this princeps study had a normal body weight, hormone variations were observed during anesthesia after short-term acute EA only, and the insulin response of normal-weight minipigs was shown to be different from that of obese subjects with basal hyperinsulinemia, higher insulin excursions, and insulin resistance [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 97%
“…Currently, whether ST36 could improve the glucose level still controversial. Some studies have suggested that EA at ST36 can improves glucose tolerance through cholinergic nerve and nitric oxide synthase effects in rats, 18,19 but some studies have also concluded the opposite, suggesting that hyperglycemia is unlikely to be responsible for the diabetes-associated depletion of ICC and maintenance of ICC requires insulin or IGF-I. 7,20,21 The reason for the inconsistency may be that the protocols were different.…”
Section: Discussionmentioning
confidence: 99%